Use of Whatsapp Application in Organizational Communications in Class II Bukittinggi Corporate Center - Nofianti, Nike; Roem, Elva Ronaning (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
Communication is very important in the continuity and success of an interaction both in everyday life and in organizational life. In the communication process, a communicator conveys a message to the communicant using the media. Media as an expansion of information is increasingly developing until emerging communication technology. Smartphones are concrete manifestations of technological advancements created to make it easier for humans to communicate. The growth of communication technology is also marked by an increase in social media. WhatsApp is one of the social media that is widely used for the purpose of socializing or as a message delivery both individuals and groups. Various facilities offered by WhatsApp, in addition to sharing messages between individuals, WhatsApp is also used for work purposes. With the various facilities and uses offered by WhatsApp, it attracts the interest of Bukittinggi Class II Rehabilitation center employees, so that employees can communicate with each other and deliver messages or information related to the tasks and functions of the agency. Therefore, researchers are interested in conducting a study entitled "Using the Whatsapp Application in Organizational Communication at Class II Rehabilitation center in Bukittinggi". This research is included in a descriptive study, which is a study conducted by collecting all key data in the form of words, pictures and data excerpts to provide an overview of the presentation of a research report. The data collection method is done through unstructured interviews and data analysis techniques are carried out using qualitative analysis methods according to Mile Hubermas (2007). From the research it was found that the Class II Rehabilitation center Bukittinggi has the main tasks namely; assistance, guidance, supervision of children in conflict with the law (ABH) and provide guidance and supervision of correctional clients as well as dealing with other law enforcement officials such as; the police, prosecutors and judges, therefore need effective communication media such as the WhatsApp application to speed up the delivery of information. so as to encourage the acceleration of the duties and functions of employees, especially in the handling of children who are dealing with the law (ABH).